2010
DOI: 10.1103/physrevlett.104.066401
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Oxidation Mechanism of a Carbon Nanotube in Nitric Acid

Abstract: Motivated by recent experiments, we investigate how NO3-SWNT interactions become energetically favorable with varying oxidation state of a single-walled carbon nanotube (SWNT) using first-principles calculations. Chemisorption becomes less endothermic with respect to physisorption when the SWNT oxidation state is elevated. Importantly, the dissociative incorporation of an oxygen atom into the SWNT sidewall becomes highly favorable when the SWNT oxidation state is elevated from electron density depletion in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 12 publications
4
35
0
Order By: Relevance
“…As mentioned previously, the charge densities used in this study, which are of the order 10 13 cm -2 of BN nanomaterial, can be easily achieved, e.g., by using electrochemical method, electrospray, electron beam or gate voltage control. [27][28][29] For example, a charge density of 7.4×10 13 In order to demonstrate the high-selectivity of negatively charged BN nanostructures for CO 2 adsorption, the adsorption energies of CH 4 and H 2 on charged and discharged 5 × 5 BN sheets and BNNTs (5,5) are calculated and compared with that of CO 2 . The results indicate that the adsorption of CH 4 and H 2 on these BN nanomaterials under all conditions considered are physical rather than chemical.…”
Section: Charge Distributions and Electron Densities Of Charged Bn Shmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, the charge densities used in this study, which are of the order 10 13 cm -2 of BN nanomaterial, can be easily achieved, e.g., by using electrochemical method, electrospray, electron beam or gate voltage control. [27][28][29] For example, a charge density of 7.4×10 13 In order to demonstrate the high-selectivity of negatively charged BN nanostructures for CO 2 adsorption, the adsorption energies of CH 4 and H 2 on charged and discharged 5 × 5 BN sheets and BNNTs (5,5) are calculated and compared with that of CO 2 . The results indicate that the adsorption of CH 4 and H 2 on these BN nanomaterials under all conditions considered are physical rather than chemical.…”
Section: Charge Distributions and Electron Densities Of Charged Bn Shmentioning
confidence: 99%
“…Here we note that the modification of the charge state of BN nanomaterials can be easily realized experimentally using electrochemical methods, electrospray, electron beam or by gate voltage control. [27][28][29] …”
Section: Introductionmentioning
confidence: 99%
“…While many density functional theory (DFT) calculations have been conducted on covalently functionalized CNTs in order to determine the influence of grafted organic groups on the electronic structure of CNTs, [46][47][48][49] to the best of our knowledge no mechanistic studies of the formation of these functional groups on CNT surface have been undertaken. Such multistep mechanistic studies are usually limited to the preliminary interaction between CNTs surfaces and atomic oxygen [50][51][52] or NO 2 + ions. [53] In the case of SWCNTs, the covalent derivatization proceeds still further, since it consists in the chemical modification of the sidewalls and tips giving rise to grafted functions such as -COOH.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy avoids complicated synthesis routes and can be easily realised experimentally using electrochemical methods, electrospray, electron beam or by gate voltage control. [35][36][37] The results have shown that after positive charges are introduced, the H 2 penetration barrier decreases while the penetration barriers of CO and CH 4 are significantly increased, hence leading to enhanced permeability and selectivity for H 2 purification from CO and CH 4 . Specifically, the penetration barriers of CO and CH 4 are increased by 32 and 7%, respectively, and the permeation of H 2 /CO and H 2 /CH 4 are 100 and 10 times higher in selectivity at room temperature.…”
mentioning
confidence: 91%